2012
DOI: 10.1007/s00213-012-2678-0
|View full text |Cite
|
Sign up to set email alerts
|

Modification of caffeine effects on the affect-modulated startle by neuropeptide S receptor gene variation

Abstract: In summary, the present findings - extending previous evidence from rodent studies - for the first time provide support for a complex, non-linear interaction of the neuropeptide S and adenosinergic systems affecting the affect-modulated startle response as an intermediate phenotype of anxiety in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…As the Ile 107 NPSR1 is associated with panic and startle responses in humans (Domschke et al, 2012), we finally determined whether intracerebroventricular NPS administration could reduce conditioned fear expression and facilitate the impaired fear extinction, respectively, in HAB rodents, as shown before in nonselected mice (Jüngling et al, 2008;Meis et al, 2008). Indeed, intracerebroventricular NPS administration was able to reduce the exaggerated fear expression seen in mHABs and to accelerate fear extinction in rHABs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the Ile 107 NPSR1 is associated with panic and startle responses in humans (Domschke et al, 2012), we finally determined whether intracerebroventricular NPS administration could reduce conditioned fear expression and facilitate the impaired fear extinction, respectively, in HAB rodents, as shown before in nonselected mice (Jüngling et al, 2008;Meis et al, 2008). Indeed, intracerebroventricular NPS administration was able to reduce the exaggerated fear expression seen in mHABs and to accelerate fear extinction in rHABs.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Npsr1 is located in a chromosomal region linked to panic disorder, and a corresponding single nucleotide poly-morphism (SNP; Asn 107 Ile-rs324981) has been associated with increased risk of the overinterpretation of fear (Okamura et al, 2007;Donner et al, 2010;Raczka et al, 2010;Domschke et al, 2011). However, while the preclinical findings to date suggest that increasing NPS levels within the brain reduces anxiety and fear responses, the human Ile 107 receptor variant exhibits increased surface receptor expression and a 10-fold higher NPSinduced signaling response than the Asn 107 variant Bernier et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A disturbed or hypersensitive arousal–anxiety relationship might be particularly relevant in individuals with anxiety disorders where hypervigilance and misinterpretation of heightened arousal is crucial (Craske & Simos, ). Consistent with this view, genetic studies have revealed a relationship of the more active rs324981 T allele of the neuropeptide S receptor ( NPSR1 ) gene with anxiety sensitivity, physiological arousal, startle response, executive function and panic disorder, particularly in women (Okamura et al ., ; Domschke et al ., , ; Beste et al ., ; Klauke et al ., ).…”
Section: Molecular Biology/geneticsmentioning
confidence: 99%
“…Genotyping for the functional neuropeptide S receptor (NPSR1) A/T (N 107 I) variant (rs324981) was performed according to published protocols Domschke et al, 2012). Genotypes were determined by investigators blinded for phenotypes and independently by two investigators.…”
Section: Genotypingmentioning
confidence: 99%